Jus Cogens Derogat Customary International Law: A Conflict that Never Was? - Muhammadin, Fajri; Afla, Anis Muhammad (Faculty of Law, Universitas Gadjah Mada, 2025)
Abstract Every scholar and learner of international law knows that jus cogens is the highest norm in the international legal order; therefore assume that “all other” sources of international law are supposed to become null and void if they contradict jus cogens. However, scholars and international institutions (including the International Law Commission) seem to overlook customary international law (CIL), easily assuming it to be part of the “all other” that are derogated by jus cogens. If we easily forget that there is virtually no actual case example of CIL contradicting jus cogens, we naturally do not ask why that is so. Exploring relevant scholarly literature as well as international documents, we explore the relationship between CIL and jus cogens. We find that one of the elements of both CIL and jus cogens overlaps, i.e. acceptance by the international community (albeit different wording), making conflict logically impossible and questions on the consequence of conflicts illogically fallacious. Abstrak Setiap cendikia dan pelajar hukum internasional mengetahui bahwa jus cogens adalah norma tertinggi dalam tatanan hukum internasional; oleh karena itu diasumsikan bahwa